Quark Confinement and the Hadron Spectrum V 2003
DOI: 10.1142/9789812704269_0001
|View full text |Cite
|
Sign up to set email alerts
|

Vortices, Confinement and Higgs Fields

Abstract: We review lattice evidence for the vortex mechanism of quark confinement and study the influence of charged matter fields on the vortex distribution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The vortex model of confinement has been buttressed by a multitude of studies, in lattice Yang-Mills theory, see e.g. [7][8][9][10][11][12][13][14][15], within the infrared effective model of center vortices under investigation here [16][17][18][19][20][21][22][23][24] and another infrared model of random vortex lines in continuous 3D space-time [25,26] and also by theoretical effective model calculations, e.g. [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The vortex model of confinement has been buttressed by a multitude of studies, in lattice Yang-Mills theory, see e.g. [7][8][9][10][11][12][13][14][15], within the infrared effective model of center vortices under investigation here [16][17][18][19][20][21][22][23][24] and another infrared model of random vortex lines in continuous 3D space-time [25,26] and also by theoretical effective model calculations, e.g. [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…While the concept of a Kertész line was originally introduced in the context of lattice gauge theories in Ref. [16], the interpretation of a deconfinement transition as driven by percolating vortices was previously put forward in the context of the SU(2) lattice Higgs model [17][18][19], and the pure SU(2) lattice gauge theory [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This theoretically appealing picture has been buttressed by a multitude of numerical calculations, both in lattice Yang-Mills theory and within a corresponding infrared effective model, see e.g. [7][8][9][10][11][12][13][14][15][16][17][18], or [19], which summarizes the main features. Recent results [20] have also suggested that the center vortex model of confinement is more consistent with lattice results than other currently available models.…”
mentioning
confidence: 99%